When a function f ( x ) is differentiated n times, the function we get is denoted f n ( x ) . If f ( x ) = x e x , find the value of n → ∞ lim ( 2 n ) ! f 2 n ( 1 )
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Relevant:
The sequence { f ( 2 ) ( 1 ) / e , f ( 4 ) ( 1 ) / e , f ( 6 ) ( 1 ) / e , f ( 8 ) ( 1 ) / e , … } and the derangement sequence are identical.
Problem Loading...
Note Loading...
Set Loading...
First, we find the power series expansion of e x and 1 / x around x = 1 : e x = e ⋅ e x − 1 = k = 0 ∑ ∞ k ! e ( x − 1 ) k x 1 = x − 1 + 1 1 = k = 0 ∑ ∞ ( − 1 ) k ( x − 1 ) k ⟹ x e x = ( k = 0 ∑ ∞ k ! e ( x − 1 ) k ) ( k = 0 ∑ ∞ ( − 1 ) k ( x − 1 ) k ) If we expand this product out, the coefficient of ( x − 1 ) n is given by k = 0 ∑ n ( − 1 ) n − k k ! e The expanded polynomial is called the Cauchy product , which converges around x = 1 since the two series both converge absolutely around x = 1 .
If we take the derivative 2 n times and evaluate at x = 1 , we get the coefficient of the ( x − 1 ) 2 n term times ( 2 n ) ! , hence ( 2 n ) ! f ( 2 n ) ( 1 ) = k = 0 ∑ 2 n ( − 1 ) 2 n − k k ! e = e k = 0 ∑ 2 n k ! ( − 1 ) k As n approaches infinity, this sum approaches e − 1 , so the result of the limit is e × e − 1 = 1 .